Analisis Kualitas Pelayanan Pada Pelayanan Terpadu Satu Pintu (Ptsp) Pengadilan Negeri Bengkulu - Endri Novian; Effed Darta Hadi; Yessy Elita (Universitas Bengkulu, 2023)
The aim of the research is to find out what the quality of the Bengkulu District Court's one-stop integrated service is and what criteria need to be improved based on priorities. The research approach is qualitative using a questionnaire distributed to selected samples. The method for analyzing the results of distributing questionnaires uses the calculation stages of Service Quality (Servqual), Importance Performance Analysis (IPA), and Potential Gain Customer Value (PGCV). The results of the research show that the perception of service users' expectations of the PTSP of the Bengkulu District Court is in the